HEPATOPROTECTIVE EFFECTS OF TANNIC ACID AGAINST CADMIUM-INDUCED OXIDATIVE STRESS: A MECHANISTIC INSIGHT - KRISHNENDU DALUI; ADRITA BANERJEE; ROMIT MAJUMDER; MADHURI DATTA; SANATAN MISHRA; AINDRILA CHATTOPADHYAY; DEBASISH BANDYOPADHYAY (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: This study explores the potential hepatoprotective effects of tannic acid (TA), a polyphenolic antioxidant, in mitigating cadmium (Cd)-induced oxidative stress in male Wistar rats. Methods: Cd was administered to induce oxidative stress-induced damage in male Wistar rats, and TA was orally fed to assess its protective role. Following the completion of the 15-day treatment period, serum organ damage markers, biomarkers of oxidative stress, activities of the Krebs’ cycle enzymes, and respiratory chain enzymes were measured. Alteration of glycogen and collagen content were histologically studied to evaluate the state of inflammation and tissue damage. Changes in mitochondrial morphology were also studied. In addition, the interaction of Cd with an important antioxidant enzyme, catalase (CAT), was also studied. Results: Rats pre-treated with TA showed significant protection against the harmful alterations caused by Cd by reducing endogenous reactive oxygen species through the control of the antioxidant defense system, inflammatory responses, and metabolic enzyme activities. Moreover, TA was also found to protect the tissue morphology and collagen deposition of the hepatic tissue and mitochondrial morphology, possibly by increasing mitochondrial viability. From isothermal titration calorimetry and circular dichroism spectroscopy studies, it is evident that TA can protect the secondary structure of CAT from being altered in the presence of Cd. Conclusion: Our results systematically demonstrate that TA provided protection against Cd-induced oxidative stress-mediated damage in rat liver tissues through its antioxidant and metal chelating mechanism(s). The results suggest the possibility of using TA alone or alongside dietary interventions in instances of oxidative stress triggered by Cd, emphasizing its potential therapeutic relevance.